Solid-Liquid-Liquid Microextraction (µSLLE) for Determining Persistent Pollutants at Marine Microplastics - García Sánchez, Yusbeli; Hernández Santana, Lionel; Abaroa Pérez, Bárbara Yolanda; Vega Moreno, Daura (2020)
Persistant organic pollutants (POPs) enter to the ocean through the air-ocean interface, or from coastal inputs, especially in the mouths of rivers and gorges [1]. Their stability and persistence, on top of their pervasiveness from man-made pollution, means that POPs can be found in almost all matrices in the environment, especially at hydrophobic matrices as microplastic [2, 3]. Microplastics with POPs over their surface, can be transported over large distances [4]. They are found in all oceanic areas over the whole world, including remote polar regions such as the Arctic Ocean. Microplastics enter by ingestion to the food chain with the subsequent bio-accumulation and bio-magnification of POPs associated [5, 6]. 318 314 Publicación correspondiente a las actas de la International Conference on Microplastic Pollution in the Mediterranean Sea (Capri, 2019) y forma parte de Springer Water book series (SPWA)